Interventional Radiologist's perspective on the management of bone metastatic disease. Issue 8 (August 2015) - Cazzato, R.L.; Buy, X.; Grasso, R.F.; Luppi, G.; Faiella, E.; Quattrocchi, C.C.; Pantano, F.; Beomonte Zobel, B.; Tonini, G.; Santini, D.; Palussiere, J.
Abstract Bone metastases can be treated by interventional radiologists with a minimally invasive approach. Such treatments are performed percutaneously under radiological imaging guidance. Different interventional techniques can be applied with curative or palliative intent depending on lesions and patients' status. In the whole, available interventional techniques are distinguished into "ablative" and "consolidative". Ablative techniques achieve bone tumor necrosis by dramatically increasing or decreasing intra-tumoral temperature. This option can be performed in order to alleviate pain or to eradicate the lesion. On the other hand, consolidative techniques aim at obtaining bone defect reinforcement mainly to alleviate pain and prevent pathological fractures. We herein present evidence supporting the application of each different interventional technique, as well as common strategies followed by interventional radiologists while approaching bone metastases.